Meeting the Needs of Low-Achieving Students in Sweden: An Interview Study - Jönsson, Anders (Frontiers in Education, 2018)
In 1994, a major curriculum reform was implemented in Sweden. A norm-referenced grading system was replaced by national goals and performance standards. The intention was that students not reaching the minimum standards would be identified and support provided. This optimistic vision has not been entirely realized. In 2017, 25.9 percent of all Swedish students graduated from compulsory school without receiving a passing grade in all subjects. To understand how students at risk of not receiving passing grades are identified and provided with support, interviews have been conducted at ten Swedish schools. Findings suggest that the schools in the sample are successful in identifying students in need of support, but not necessarily in identifying the specific needs of individual students. The identification may also differ between students with learning difficulties and students with behavioral problems. Furthermore, the findings suggest that schools and teachers in the sample have different approaches when providing support to low-achieving students. This support can be categorized as supporting and relational, simplifying, or general and practical. These approaches, in turn, may provide different opportunities for students’ engagement with schoolwork and eventually their performance. By discussing the findings in relation to self-determination theory and self-efficacy, the combination of challenging tasks and scaffolding support, as well as providing structure in combination with caring relationships, were identified as important facilitators of increased student motivation and effort.